Uma proposta de integração entre a abordagem kaleckiana da distribuição setorial funcional da renda e a teoria schumpeteriana do processo de concorrência - Melo, Tatiana Massaroli de [UNESP] (My University, 2014)
This paper uses a theoretical schumpeterian and kaleckian to analyze the dynamic effects of innovation on competitiveness and sectoral functional income distribution. By affecting the mark-up and market power successful innovations allow the expansion of the asymmetries between firms, intensifying competition and promoting mismatches in sectoral income distribution between wages and profits.

Este artigo utiliza um referencial teórico schumpeteriano e kaleckiano para analisar os efeitos dinâmicos das inovações sobre a competitividade e a distribuição setorial funcional da renda. Ao afetar o mark-up e o poder de mercado as inovações bem sucedidas permitem a ampliação das assimetrias entre as firmas, intensificando a concorrência e promovendo desajustes na distribuição da renda setorial entre salários e lucros.
A proposal of integration between the kaleckian approach of the sectoral functional income distribution and the schumpeterian theory of the competition process
Keywords: Sectoral functional income distribution; Competition process; Innovation; Distribuição setorial funcional da renda; Processo de concorrência; Inovação